The Blackwell companion to religion and violence - Murphy, Andrew R., 1967- (Chichester, West Sussex : Wiley-Blackwell, 2011)
'The timely Blackwell Companion to Religion and Violence brings together an international, interdisciplinary group of scholars who provide a coherent state of the art overview of the complex relationships between religion and violence. This Companion tackles one of the most important topics in the field of Religion in the twenty-first century, pulling together a unique collection of cutting-edge work A focused collection of high-quality scholarship provides readers with a state-of-the-art account of the latest work in this field. The contributors are broad-ranging, international, and interdisciplinary, and include historians, political scientists, religious studies scholars, sociologists, anthropologists, theologians, scholars of women's and gender studies and communication.'--
'The Blackwell Companion to Religion and Violence offers a state-of-the-art overview of this diverse and crucially important subject. This timely volume brings together an international, interdisciplinary group of scholars who probe the complex relationship between religion and violence, now and in the past. Media accounts often announce the inherent connections between'fanatical' believers and terroristic violence; but scholars have long recognized that such links are only one small part of a larger and more complex set of interactions. They argue that religious beliefs and practices are just as likely to provide resources for comfort and coping as to encourage violence and carnage. The volume is divided into several major sections: Traditions and Movements, Disciplinary Perspectives, Concepts and Themes, and Case Studies, which explore specific incidences of both religious violence and instances where religion has contributed to the resistance of violence. A concluding section offers insights into the future direction of scholarship in the area. It also includes discussions of the ongoing importance of religion to terrorism, and religious competition and conflict in Africa. Each section offers high-quality, cutting-edge scholarship, as leading authorities seek to make sense of the problematic correlation between these two forces'--
Includes bibliographical references and index.
Keywords: Violence -- Religious aspects